A Framework Proposal for Plan Evaluation in the Context of Turkish Planning System - Ibisoglu, Cigdem; Ozugul, Mehmet Doruk (KONYA TECHNICAL UNIV, FAC ARCHITECTURE & DESIGN, 2022)
This study aims to propose a framework for plan evaluation in the context of Turkish planning system???s structural characteristics. Within the scope of the study, main planning evaluation approaches (conformance-based and performance -based) were examined, and prominent evaluation methods were analyzed in detail. Then, type of planning systems and the major breaking points in changing process of planning system in Turkey are summarized. With reference to these issues, a filtered framework that can be used for plan evaluation in Turkey has been suggested. In this research, it has been concluded that the plan evaluation can be realized in three main dimensions and some sub-criteria: conformity (plan and output accordance, plan effects, relevance), rationality (internal coherence, external coherence, participation, cooperation and coordination), utilisation (guidance or direction). Although it provides an applicable framework, the suggestion does not offer a method that can be applied one-to-one for each plan. Under the rapidly changing conditions in our country, the evaluation criterion should be reconfigured in line with the features of relevant plan. It is foreseen that a basic monitoring mechanism can be created for planning institution by using the framework in this study. Also, it will provide self-evaluation opportunities for planning authorities. In this way, we believe that the success level of plans and planning system will increase. Evaluation of plan is an important research area in the international literature in terms of both qualitative and quantitative elements to be analyzed together. However, it is not yet included in Turkish planning literature. Therefore, this study is valuable as it highlights a new research area by pointing to an important gap in the national planning literature. It is thought that this study has original contributions to both theory and practice and will establish a functional bridge between them.
Keywords: Conformance-based approach; evaluation in planning; performance-based approach plan evaluation framework; planning system; LOCAL PLANS; IMPLEMENTATION; CONFORMANCE; FLEXIBILITY; OUTCOMES; Architecture